PHYSICAL ACTIVITY AND ADHD: EVIDENCE ON DEVELOPMENT, TRANSIENT AND DURABLE NEUROCOGNITIVE EFFECTS, AND APPLICATIONS - María Enid Santiago Rodriguez; Jared Donald Ramer; Guilherme M. Balbim; Tara Gisela Mehta; Stacy Lynn Frazier (Universidad de Costa Rica, 2019)
Bustamante, E.E, Santiago-Rodríguez, M., Ramer, J.D., Balbim, G.M., Metha, T. & Frazier, S.L. (2019). PENSAR EN MOVIMIENTO: Revista de Ciencias del Ejercicio y la Salud, 17(1), 1-25.Attention-Deficit/Hyperactivity Disorder (ADHD) is characterized by neurodevelopmental delays. Physical activity (PA) may influence many of the same neurocognitive systems affected by ADHD. Therefore, PA may be a potential tool in treatment and management plans. This review synthesizes findings from studies investigating PA, fitness, and motor coordination. Studies of PA in youth on the spectrum for ADHD were considered in this paper. Main results include: a) cross-sectional studies: children with ADHD evidence PA levels higher than children that seem to be healthy. Childhood coincides with opportunities to free play; however, this advantage dissipates by adolescence, as PA programs become increasingly structured and less inclusive. In adulthood, individuals with ADHD are more likely to be obese and less likely to meet healthy lifestyle guidelines; b) longitudinal studies: PA at earlier stages predicts symptom severity in subsequent stages; and c) further studies: moderate PA activity of limited duration offers neurocognitive benefits. Multi-week intervention studies have tested diverse formats with results that differ based upon the chosen outcome and comparison group utilized. PA interventions that challenge cognition and fundamental movement skills in childhood provide benefits to children with ADHD. They also encourage children and adolescents to participate in structured programs, meet PA guidelines, and include short-term AF as part of daily routines.